2024
DOI: 10.3389/fpubh.2024.1250085
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality, quality of life, fatigue, and mental health in COVID-19 post-pandemic Türkiye: a cross-sectional study

Abdulbari Bener,
Ebru Morgul,
Mahmut Tokaç
et al.

Abstract: AimThis study explores the predictors and associated risk factors of sleep quality, quality of life, fatigue, and mental health among the Turkish population during the COVID-19 post-pandemic period.Materials and methodsA cross-sectional survey using multi-stage, stratified random sampling was employed. In total, 3,200 persons were approached. Of these, 2,624 (82%) completed the questionnaire package consisting of socio-demographic information, Pittsburgh Sleep Quality Index (PSQI), the WHO Quality of Life Brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This evidence is in line with recent findings from Turkey reporting a significant level of sleep disorders, fatigue, and depressive-anxious symptoms in the general population during the post-pandemic phase in 2022 [28]. In fact, the authors concluded that unsatisfactory sleep quality seemed to affect physical and mental health functioning in the general population [29]. Sleeping abnormalities have been broadly described as affecting the general population during the pandemic's lockdown phase (not only in Turkey), particularly among people affected by COVID-19 [2,4,21].…”
Section: Discussionsupporting
confidence: 91%
“…This evidence is in line with recent findings from Turkey reporting a significant level of sleep disorders, fatigue, and depressive-anxious symptoms in the general population during the post-pandemic phase in 2022 [28]. In fact, the authors concluded that unsatisfactory sleep quality seemed to affect physical and mental health functioning in the general population [29]. Sleeping abnormalities have been broadly described as affecting the general population during the pandemic's lockdown phase (not only in Turkey), particularly among people affected by COVID-19 [2,4,21].…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, our analysis of Bener et al (1) study delves into the enduring impact of the COVID-19 pandemic on the mental health and sleep quality of the Turkish population. Emphasizing the need to prioritize interventions that enhance sleep quality as a crucial aspect of public health, our findings propose potential avenues for mitigating or preventing the onset of mental health disorders.…”
Section: Discussionmentioning
confidence: 82%